2017
DOI: 10.1038/s41467-017-00311-2
|View full text |Cite
|
Sign up to set email alerts
|

The non-coding RNA BC1 regulates experience-dependent structural plasticity and learning

Abstract: The brain cytoplasmic (BC1) RNA is a non-coding RNA (ncRNA) involved in neuronal translational control. Absence of BC1 is associated with altered glutamatergic transmission and maladaptive behavior. Here, we show that pyramidal neurons in the barrel cortex of BC1 knock out (KO) mice display larger excitatory postsynaptic currents and increased spontaneous activity in vivo. Furthermore, BC1 KO mice have enlarged spine heads and postsynaptic densities and increased synaptic levels of glutamate receptors and PSD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…Phenotypic alterations in BC1 KO animals ( Zhong et al, 2009 ; Briz et al, 2017 ; Iacoangeli et al, 2017 ) are caused by global lack of regulatory BC1 RNA. It was formally possible that phenotypic alterations in CGG animals were also caused by a reduction of brain BC1 RNA expression levels, in addition to cellular BC1 RNA mislocalization as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic alterations in BC1 KO animals ( Zhong et al, 2009 ; Briz et al, 2017 ; Iacoangeli et al, 2017 ) are caused by global lack of regulatory BC1 RNA. It was formally possible that phenotypic alterations in CGG animals were also caused by a reduction of brain BC1 RNA expression levels, in addition to cellular BC1 RNA mislocalization as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Novel object recognition experiments were conducted in a 30 cm × 30 cm × 20 cm field arena. For the object recognition test, we adapted a protocol previously described in several studies ( Bevins and Besheer, 2006 ; Leger et al, 2013 ; Briz et al, 2017 ; Volmar et al, 2017 ). The test comprised training and testing phases.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Briz et al confirmed that a BC1 deficiency causes expression imbalances in the postsynaptic region, promoting an abnormal expression of glutamate receptor subunits that results in excessive signal transmission. The resulting hyperexcitation of neurons extinguishes synaptic plasticity, leading to severe defects in cognition and learning [62].…”
Section: Functions Of Bc Rnasmentioning
confidence: 99%